Exam design with integration of graphic organizers based on the taxonomy of the digital age - Amorocho Abril, Esmer Leonel (Rastros Rostros, 2024)
Introduction: The subject of Information Technology (IT) has been subject to changes in public policy and has not been well understood in its design, implementation and evaluation, which raises concerns about the lack of standardized criteria for the evaluation of it learning in students of secondary education.Objective: Design effective exams with the integration of graphic organizers based on digital taxonomy and a psychometric model in the Secondary Education of an Educational Institution in the municipality of Piedecuesta (Colombia).Methodology: A quantitative approach and a quasi-experimental design are adopted, dividing 218 participating students into control and experimental groups. The treatments include didactic sequences in it education, followed by electronic tests to evaluate learning. Data collection is carried out using the Limesurvey platform, and analysis of dichotomous data matrices with various graphic organizers is used. Reagents are constructed following a new taxonomy and their psychometric characteristics are evaluated, adapting them according to the results observed by groups. Calibration of reagents is carried out with the Rash model. Results and discussion: Sample contrasts revealed that, in general, there are no significant differences between experimental and control groups, except in one experiment that requires additional model calibration. Calibration by Rash reagents, using software such as MiniStep, showed adequate adjustments in INFIT and OUTFIT statistics, indicating good fit to the model.Conclusions: The implementation of electronic tests with graphic organizers in Secondary Education is shown to be effective in improving the evaluation in Information Technology, supported by positive student perceptions. This methodology facilitates the evaluation of learning, provides standardized and reliable results, allowing precise monitoring of learning processes in the IT subject.
Keywords: Secondary education; psychometric model; graphic organizers; digital taxonomy; computer technology